The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ijgo.13092
|View full text |Cite
|
Sign up to set email alerts
|

Advocating safe abortion: outcomes of a multi‐country needs assessment on the potential role of national societies of obstetrics and gynecology

Abstract: In 2019 the International Federation of Gynecology and Obstetrics (FIGO) embarked on an initiative that aims to strengthen the capacity of 10 national societies of obstetrics and gynecology (ObGyn) in advocacy for safe abortion. In 2018 needs assessments that entailed a desk study, interviews, and stakeholder workshops were conducted in Benin, Cameroon, Côte d'Ivoire, Kenya, Mali, Mozambique, Panama, Peru, Uganda, and Zambia. The general aim of the needs assessments was to gain a deeper understanding of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“… 34 Furthermore, previous studies have suggested that abortion is highly stigmatized in Uganda. 35 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“… 34 Furthermore, previous studies have suggested that abortion is highly stigmatized in Uganda. 35 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…The legal framework related to pregnancy termination differs in the two countries which could explain those differences. It is semiliberalized in Benin and restrictive in Mali [49]. In Mali, therapeutic abortion is permitted only in case of incest, fetal malformation, or risk for the mother's life.…”
Section: Discussionmentioning
confidence: 99%
“…In Benin, women can access therapeutic abortion to protect their health. However, it is not because the legal framework is more liberalized that the access to safe abortion is easier [49].…”
Section: Discussionmentioning
confidence: 99%
“…In Benin, private health centers are known to provide therapeutic abortion services. They are mostly centralized around Cotonou [40]. In Benin, the cost of a therapeutic abortion was estimated at between 24.50-89.00 US dollars [45].…”
Section: Do Sex Workers Have As Many Pregnancies During Their Sex Wormentioning
confidence: 99%
“…The legal framework related to pregnancy termination differs in the two countries which could explain those differences. It is semi-liberalized in Benin and restrictive in Mali [40].…”
Section: Do Sex Workers Have As Many Pregnancies During Their Sex Work Practice As Prior To It?mentioning
confidence: 99%